2020
DOI: 10.4103/jfmpc.jfmpc_663_20
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess undernutrition and its sociodemographic correlates in under-five children in urban and rural areas of Rishikesh, Uttarakhand

Abstract: Context: Nutrition is one of the most important factors that affect a child's health. It plays a vital role in the prevention and control of disease morbidity and mortality. It is a major public health problem in a developing country like India. Aims: To assess undernutrition in under-five children and various sociodemographic factors affecting it. Settings and Design: A community-based cross-sectional study was conducted among under-five chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Malnutrition was the principal risk factor for death in under-five children in every state of India in 2017, accounting for 68% of the total under-five deaths (Swaminathan et al, 2019). Earlier studies found various socioeconomic and demographic factors such as age and gender of the child (Bharati et al, 2008), maternal education (Meshram et al, 2012; Mukherjee et al, 2008; Sen et al, 2011) and BMI (Corsi et al, 2016), family size (Rehan et al, 2020; Swami et al, 2000), household wealth status (Corsi et al, 2016; Kanjilal et al, 2010; Meshram et al, 2012), housing condition (Som et al, 2007), religion & caste (Rehan et al, 2020), place of residence and region (Bharati et al, 2008), and state-level dietary diversity (Borkotoky et al, 2018) affecting the nutritional status of under-five children in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition was the principal risk factor for death in under-five children in every state of India in 2017, accounting for 68% of the total under-five deaths (Swaminathan et al, 2019). Earlier studies found various socioeconomic and demographic factors such as age and gender of the child (Bharati et al, 2008), maternal education (Meshram et al, 2012; Mukherjee et al, 2008; Sen et al, 2011) and BMI (Corsi et al, 2016), family size (Rehan et al, 2020; Swami et al, 2000), household wealth status (Corsi et al, 2016; Kanjilal et al, 2010; Meshram et al, 2012), housing condition (Som et al, 2007), religion & caste (Rehan et al, 2020), place of residence and region (Bharati et al, 2008), and state-level dietary diversity (Borkotoky et al, 2018) affecting the nutritional status of under-five children in the country.…”
Section: Introductionmentioning
confidence: 99%
“…The studies on prevalence of malnutrition in underfive children was evaluated and results found were: in Rishikesh underweight, stunting and wasting was 37.3%, 43.3% and 24.5% respectively [11] , in Haridwar 44.82% stunted and 51.72% were underweight [12] , in Kashipur it was found that about 27.27% and 54.55% children in the age group of (0-5) years were found malnourished in mild to moderate category [13] and in Dehradun it was found that 200 (52.5%) children having exclusively breast fed were undernourished [14] .…”
Section: Uttarakhandmentioning
confidence: 99%
“…illiterate parents had more percentage of malnourished children. [11,12,18] Occupation of parents [11,17,19] and size of family [19] .…”
Section: Socio Demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…2020). [ 9 ] 43.3% in Dehradun, 59% in Kolkata (Scopazzini M. et al . 2021),[ 10 ] This indicates inequalities in the reduction of stunting in different parts of the country.…”
Section: Introductionmentioning
confidence: 99%